2017
DOI: 10.1021/acs.joc.7b02148
|View full text |Cite
|
Sign up to set email alerts
|

Copper-Catalyzed Azidative Multifunctionalization of Alkynes

Abstract: A facile and efficient copper-catalyzed azidative multifunctionalization of alkynes has been developed by using N-fluorobenzenesulfonimide (NFSI) as both nitrogen source and aryl source and trimethylsilyl azide (TMSN) as azido source. This transformation proceeds under mild conditions, providing a series of α-azido-α-aryl imine in good yields by a single operation starting from a wide range of alkynes. The prepared α-azido-α-aryl imines could be easily converted into 1,5-piperizine-fused 1,2,3-triazoles and az… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Based on these experimental results and literature precedents, , we propose the following tentative reaction mechanism. The transformation started with the oxidation of Cu­(II) to Cu­(III) complex by NFSI.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Based on these experimental results and literature precedents, , we propose the following tentative reaction mechanism. The transformation started with the oxidation of Cu­(II) to Cu­(III) complex by NFSI.…”
mentioning
confidence: 61%
“…In view of this above-mentioned synthetic gap and our interest in radical reactions, we hence decided to focus on the ketone synthesis from simple alkyne cleavage using earth-abundant copper catalysts . At the onset of our project, we noticed in the literature that the combination of copper catalyst and NFSI ( N -fluorobenzenesulfonimide) effectively enabled the addition of N -radicals to alkynes, and the resulting activated vinyl radical species upon aryl migration could afford a variety of multifunctionalized products . Notwithstanding such progress, we questioned whether incorporating extra oxidants could facilitate the cleavage of Cu/NFSI-activated alkyne intermediates to furnish the overall alkyne cleavage products.…”
mentioning
confidence: 99%
“…In the course of their endeavors, Zhang et al. discovered that imines 135 - 5 could be obtained in good yields when the mixture of simple internal alkyne 135 - 1 , NFSI, and TMSN 3 was exposed to 5 mol % of CuCl and 5 mol % of N-containing bidentate Phen in DCE at 70 °C (Scheme A) . Mechanistic investigation showed that the in situ generated α-aryl-α-imino carbon radical 135 - 11 will recombine with Cu­(II) species to yield organocopper­(III) species 135 - 12 (Scheme B).…”
Section: Radical-mediated Desulfonylation Of N-containing Sulfonyl De...mentioning
confidence: 99%
“…Zheng et al [21] . described a facile and efficient copper‐catalyzed azidative multifunctionalization of various internal alkyne 42 by using of NFSI ( N ‐fluorobenzene sulphonimide) and TMSN 3.…”
Section: Synthesis Of Fused 123‐triazolesmentioning
confidence: 99%